2021
DOI: 10.1038/s41535-021-00316-7
|View full text |Cite
|
Sign up to set email alerts
|

Quantum spin liquid and cluster Mott insulator phases in the Mo3O8 magnets

Abstract: We unveil the microscopic origin of largely debated magnetism in the Mo3O8 quantum systems. Upon considering an extended Hubbard model at 1/6 filling on the anisotropic kagomé lattice formed by the Mo atoms, we argue that its ground state is determined by the competition between kinetic energy and intersite Coulomb interactions, which is controlled by the trimerisation of the kagomé lattice into the Mo3O13 clusters, and the sign of hopping parameters, specifying the electron localisation at such clusters. Base… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…It has been postulated that the magnetic behavior may show features of a resonating valence-bond state, 22,23 dimerization, 24 or plaquette charge order. 25,26 Recently, we showed that the breathing kagome-network compound LiScMo 3 O 8 (Figure 1a), a diamagnetic insulator because of complete localization of two d electrons per Mo within Mo−Mo bonds, is an effective anode material for Li-ion batteries. 27 The related compound Li 2 ScMo 3 O 8 (Figure 1b), with an extra d electron for every 3 Mo, also possesses a Mobased breathing kagome network, shown in Figure 1c, and is reported to be a frustrated cluster magnet, 28 with little sign of long-range magnetic order down to T = 0.5 K. Li 2 In 1−x Sc x Mo 3 O 8 , in contrast, where Sc is replaced by the smaller, isoelectronic In, has been noted to show antiferro-magnetic long-range order through muon spin rotation experiments.…”
Section: ■ Introductionmentioning
confidence: 99%
“…It has been postulated that the magnetic behavior may show features of a resonating valence-bond state, 22,23 dimerization, 24 or plaquette charge order. 25,26 Recently, we showed that the breathing kagome-network compound LiScMo 3 O 8 (Figure 1a), a diamagnetic insulator because of complete localization of two d electrons per Mo within Mo−Mo bonds, is an effective anode material for Li-ion batteries. 27 The related compound Li 2 ScMo 3 O 8 (Figure 1b), with an extra d electron for every 3 Mo, also possesses a Mobased breathing kagome network, shown in Figure 1c, and is reported to be a frustrated cluster magnet, 28 with little sign of long-range magnetic order down to T = 0.5 K. Li 2 In 1−x Sc x Mo 3 O 8 , in contrast, where Sc is replaced by the smaller, isoelectronic In, has been noted to show antiferro-magnetic long-range order through muon spin rotation experiments.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Another mixed metal system with exciting properties and curious hybridization is Fe 2 Mo 3 O 8 -also known as the mineral Kamiokite [11]. While magnetism and magnetoelectric coupling have been widely studied [12][13][14][15][16][17][18][19], the charge excitations are highly under-explored.…”
Section: Introductionmentioning
confidence: 99%
“…Fe 2 Mo 3 O 8 is a polar magnet with giant magnetoelectric coupling, strong Dzyaloshinski-Moriya interactions, valence bond condensation (creating a cluster magnet), and the possibility of orbitally-selective transitions [12][13][14][15][16][17][18][19]. Zinc substitution, first on the tetrahedral Fe site and then on the octahedral Fe site [15,20], is of inter-est for magnetic properties as well [11,13,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Another mixed metal system with exciting properties and curious hybridization is Fe 2 Mo 3 O 8 -also known as the mineral kamiokite [11]. While magnetism and magnetoelectric coupling have been widely studied [12][13][14][15][16][17][18][19], the charge excitations are highly underexplored.…”
Section: Introductionmentioning
confidence: 99%
“…Fe 2 Mo 3 O 8 is a polar magnet with giant magnetoelectric coupling, strong Dzyaloshinski-Moriya interactions, valence bond condensation (creating a cluster magnet), and the possibility of orbitally selective transitions [12][13][14][15][16][17][18][19]. Zinc substitution, first on the tetrahedral Fe site and then on the octahedral Fe site [15,20], is of interest for magnetic properties as well [11,13,20,21].…”
Section: Introductionmentioning
confidence: 99%